Anti-complement 5 antibody ameliorates antibody-mediated rejection after liver transplantation in rats - Tajima, Tetsuya; Hata, Koichiro; Kusakabe, Jiro; Miyauchi, Hidetaka; Badshah, Joshua Sam; Kageyama, Shoichi; Zhao, Xiangdong; Kim, Sung-Kwon; Tsuruyama, Tatsuaki; Kirchner, Varvara A.; Watanabe, Takeshi; Uemoto, Shinji; et al. (Frontiers in Immunology, 2023)
Antibody-mediated rejection (AMR) remains a refractory rejection after donor-specific antibody (DSA)-positive or blood-type incompatible liver transplantation (LT), even in the era of pre-transplant rituximab desensitization. This is due to the lack of not only effective post-transplant treatments but also robust animal models to develop/validate new interventions. Orthotopic LT from male Dark Agouti (DA) to male Lewis (LEW) rats was used to develop a rat LT-AMR model. LEW were pre-sensitized by a preceding skin transplantation from DA 4–6 weeks before LT (Group-PS), while sham procedure was performed in non-sensitized controls (Group-NS). Tacrolimus was daily administered until post-transplant day (PTD)-7 or sacrifice to suppress cellular rejections. Using this model, we validated the efficacy of anti-C5 antibody (Anti-C5) for LT-AMR. Group-PS+Anti-C5 received Anti-C5 intravenously on PTD-0 and -3. Group-PS showed increased anti-donor (DA) antibody-titers (P <0.001) and more C4d deposition in transplanted livers than in Group-NS (P <0.001). Alanine aminotransferase (ALT), alkaline phosphatase (ALP), total bile acid (TBA), and total bilirubin (T-Bil) were all significantly higher in Group-PS than in Group-NS (all P <0.01). Thrombocytopenia (P <0.01), coagulopathies (PT-INR, P =0.04), and histopathological deterioration (C4d+h-score, P <0.001) were also confirmed in Group-PS. Anti-C5 administration significantly lowered anti-DA IgG (P <0.05), resulting in decreased ALP, TBA, and T-Bil on PTD-7 than in Group-PS (all P <0.01). Histopathological improvement was also confirmed on PTD-1, -3, and -7 (all P <0.001). Of the 9,543 genes analyzed by RNA sequencing, 575 genes were upregulated in LT-AMR (Group-PS vs. Group-NS). Of these, 6 were directly associated with the complement cascades. In particular, Ptx3, Tfpi2, and C1qtnf6 were specific to the classical pathway. Volcano plot analysis identified 22 genes that were downregulated by Anti-C5 treatment (Group-PS+Anti-C5 vs. Group-PS). Of these, Anti-C5 significantly down-regulated Nfkb2, Ripk2, Birc3, and Map3k1, the key genes that were amplified in LT-AMR. Notably, just two doses of Anti-C5 only on PTD-0 and -3 significantly improved biliary injury and liver fibrosis up to PTD-100, leading to better long-term animal survival (P =0.02). We newly developed a rat model of LT-AMR that meets all the Banff diagnostic criteria and demonstrated the efficacy of Anti-C5 antibody for LT-AMR.